Peningkatan Kemampuan Penalaran Matematis dan Kemandirian Belajar Siswa Madrasah Tsanawiyah (MTs) melalui Pendekatan Contextual Teaching and Learning (CTL) - Nuridawani Nuridawani; Said Munzir; Saiman Saiman (Didaktik Matematika, 2015)
Mathematical reasoning ability and self-regulated learning is one of the objectives of the mathematics learning that should be owned by the students. It is needed relevant learning approaches to develop and improve mathematical reasoning ability and self-regulated learning. One of the learning approaches is Contextual Teaching and Learning (CTL). The purpose of this study was to determine: the improvement of mathematical reasoning ability and self-regulated learning of students who obtain CTL approach and students who receive conventional learning. This study was an experimental research study designed by pretest-posttest control group design. The population of this study was all students of class VII MTsN Rukoh Banda Aceh. While the sample was composed of two classes, namely the experimental class and control class taken by random sampling. The instruments used to obtain research data were the form of mathematical reasoning ability tests and questionnaires of students learning independence. To see the difference in mathematical reasoning ability and self-regulated learning between CTL approach classesand conventional classes used the t-test at the 0.05 significance level. Based on this research, it was known that 1) the improvement of mathematical reasoning ability of studentsacquire learning CTL approach better than students who received conventional learning approaches; 2) the improvement of students independence learning gained CTL approach better than received conventional approaches. CTL approach in learning can affect the better ability of mathematical reasoning and self-regulated learning, in terms of quality there was a significant difference between students who are learning using CTL approach and using conventional learning.